2021
DOI: 10.1001/jama.2021.12966
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Stroke Thrombolysis in the US by Race and Ethnicity, 2009-2018

Abstract: Lower rates of intravenous (IV) thrombolysis use after stroke in Black and Hispanic individuals have been described in the US. [1][2][3][4][5][6] However, it is unclear whether the disparities gap in thrombolysis use is changing or remaining the same. We investigated the temporal trend in racial and ethnic differences in stroke IV thrombolysis use between 2009 and 2018 in a representative sample of US adults.Methods | Adult hospital discharges with a primary diagnosis of ischemic stroke were identified from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Stroke Ready was conducted in Flint, which is comprised of predominantly Black people (54%) and over 40% of the population lives below the poverty level. The Stroke Ready program was a multilevel intervention that included (1) an emergency department implementation science-based intervention to optimize acute stroke care and (2) community intervention including community engagement, peer leaders, and multimedia strategies to increase stroke preparedness. 3 Stroke Ready was associated with a nonstatistically significant increase in thrombolysis treatment rates (odds ratio, 1.13 [95% CI, 0.74-1.70]; P=0.58).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke Ready was conducted in Flint, which is comprised of predominantly Black people (54%) and over 40% of the population lives below the poverty level. The Stroke Ready program was a multilevel intervention that included (1) an emergency department implementation science-based intervention to optimize acute stroke care and (2) community intervention including community engagement, peer leaders, and multimedia strategies to increase stroke preparedness. 3 Stroke Ready was associated with a nonstatistically significant increase in thrombolysis treatment rates (odds ratio, 1.13 [95% CI, 0.74-1.70]; P=0.58).…”
Section: Methodsmentioning
confidence: 99%
“…
lack people receive less stroke thrombolysis than White people. 1 We conducted Stroke Ready, a stroke preparedness intervention, first as a small-scale pilot study from 2010 to 2015 2 and then city-wide in Flint, MI, from October 2017 to March 2020. 3 Between 2010 and 2020, Flint transformed from a low-performing region to a high-performing region for stroke thrombolysis.
…”
mentioning
confidence: 99%
“…In addition, there have been reports of racial and ethnic disparities of thrombolysis use in stroke in the past decade . A study of National Inpatient Sample 2004-2010 data showed that among patients hospitalized for ischemic stroke, without accounting for presentation timeliness, Black and Hispanic patients were less likely to be treated with IVT than White patients .…”
Section: Introductionmentioning
confidence: 99%
“…A study of National Inpatient Sample 2004-2010 data showed that among patients hospitalized for ischemic stroke, without accounting for presentation timeliness, Black and Hispanic patients were less likely to be treated with IVT than White patients . Another study using later 2009-2018 National Inpatient Sample data showed improvements but that Black individuals continued to receive less thrombolytic treatment than White individuals . The administrative data studies had limitations, including an inability to examine the contributions of time of presentation to observed rates of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with a lower likelihood of tPA declination were treatment at a teaching hospital, larger annual IV tPA volume, and longer times from onset to arrival (but only among those arriving >90 minutes after symptom onset).These race-and gender-based differences in declination of tPA for ischemic stroke align well with previous data demonstrating disparities in stroke care, including tPA administration and other quality measures. [2][3][4][5] This study adds to that knowledge and suggests that tPA declination may differ by demographic group (and specifically is higher among women and Black individuals). When considering the role of patient declination in disparities in acute stroke care, we must interpret this finding using a patient-centered perspective and in the context of a health care system in which there are structural and interpersonal racism, lack of racial diversity in the health care workforce, and individual unconscious bias among providers.…”
mentioning
confidence: 98%